Absorption of ethyl 2-cyanoacrylate tissue adhesive - (:unkn) unknown (MEDECINE ET HYGIENE, 2004)
The aim of this study was to investigate absorption of ethyl 2-cyanoacrylate glue when used as a tissue adhesive. Ethyl 2-cyanoacrylate was applied subcutaneously to four rats; its presence in blood and urine was investigated by using High Pressure Liquid Chromatography. Blood samples were drawn at baseline and after 2, 4, 6, 24, 48, 54, 78, 96 hours following application. Urine samples were obtained at baseline and after 4, 24, 48, 72, 96 hours. Administration of ethyl 2-cyanoacrylate resulted in its absorption of unchanged ethyl 2-cyanoacrylate and unknown metabolites, in plasma and urine.
Keywords: ethyl 2-cyanoacrylate; tissue adhesive; high pressure liquid chromatography analysis; IDENTIFICATION; METABOLISM; ACID; RATS